Antibody responses in blood and saliva post COVID-19 bivalent booster do not reveal an Omicron BA.4/BA.5- specific response - Baker, Ryan; Lawlor, Rebecca; Smith, Maeve; Price, Jessica; Eaton, Ashley; Lover, Andrew; Alfandari, Dominique; Reinhart, Peter; Arcaro, Kathleen F.; Osborne, Barbara A. (Frontiers in Immunology, 2024)
Formatted: Portuguese (Brazil) Formatted: Portuguese (Brazil) Current SARS-CoV-2 strains continue to mutate and attempt to evade the antibody response elicited by previous exposures and vaccinations. In September of 2022, the first updated SARS-CoV-2 vaccines, designed to create immune responses specific for the variants circulating in 2022, were approved. These new vaccines, known commonly as the bivalent boost(er), include mRNA that encodes both the original Wuhan-Hu-1 spike protein as well as the spike protein specific to the Omicron BA.4 and BA.5 variants. For the first time, we provide a comprehensive analysis of the antibody response following a single dose of the bivalent boost over a 6-month period. Our data support previous findings that the response induced after the bivalent boost does not create a strong BA.4/BA.5-specific antibody response. We also find no evidence of a specific anti-BA.4/BA.5 response developing over time, including in a sub-population of individuals who become infected after a single dose of the bivalent booster. Additionally, we present data that support the use of saliva samples as a reliable alternative to blood for antibody detection against specific SARS-CoV-2 antigens.